STRATEGIES FOR THE PREVENTION OF KNEE INJURIES IN SOCCER ATHLETES: INTEGRATIVE REVIEW (Movimenta (ISSN 1984-4298), 2023)
Introduction: Soccer is one of the most popular sports in the world and requires players to have high impact physical contact during sports practice, which can lead to lower limb injuries, most commonly knee injuries. Objective: To identify physiotherapeutic programs and strategies for the prevention of knee injuries in soccer players. Materials and methods: This is an integrative review of the literature based on a research protocol and the recommendations Statement for Reporting Systematic and Meta-Analyses of Studies (PRISMA), through the databases LILACS, MEDLINE, PubMed and SciELO, which culminated in the selection of six scientific articles on the researched theme. Results: From the data analyzed, it was found that the Knee Control, FIFA 11+, MC-7 multifactorial program, PEP program and a proprioceptive training strategy were used for knee injury prevention in soccer athletes. Conclusion: This review identified that the FIFA 11+ and Knee Control programs have significant results for the prevention of these injuries in soccer athletes.
Keywords: Soccer.; Knee injuries; Prevention